1999
DOI: 10.1111/j.1095-8649.1999.tb00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cortisol and 17β‐oestradiol levels in roach exposed to acute and chronic stress

Abstract: Article (refereed) -postprintPottinger, T.G.; Yeomans, W.E.; Carrick, T.R.. 1999 Plasma cortisol and 17β-estradiol levels in roach exposed to acute and chronic stress. Journal of Fish Biology, 54 (3). 525-532. 10.1111/j.1095-8649.1999.tb00633.x Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. 1Plasma cortisol and 17β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“… (a) Mean values for plasma cortisol levels in six cyprinid and eight salmonid species subjected to a range of stressors. The data plotted were obtained from: Aaltonen et al (2000); Barton (2000); Basu et al (2001); Bau et al (2001); Benfey & Biron (2000); Blahová et al (2007); Cairns et al (2008); Clements et al (2002); Congleton et al (2000); Dabrowska et al (1991); Davis & Schreck (1997); Dror et al (2006); Einarsdóttir & Nilssen (1996); Elofsson et al (2000); Fevolden et al (1999); Gagnona et al (2006); Høgåsen & Prunet (1997); Iversen et al (1998); Jeney et al (1996); Jhingan et al (2003); Jørgensen et al (2001, 2002); Kagawa & Mugiya (2000); Kakuta (1998); Kubokawa et al (1999); Lister et al (2008); McDonald & Robinson (1993); McDonald et al (1993); Mesa (1994); Mesa et al (2000); Momoda et al (2007); Øverli et al (1999); Pankhurst & Dedual (1994); Pankhurst et al (2008); Pickering et al (1982, 1986); Pottinger & Carrick (2000); Pottinger & Moran (1993); Pottinger (1998); Pottinger et al (1992, 1999, 2000); Quabius et al (2000); Quigley et al (2006); Reddy et al (1995); Ruane et al (1999, 2001, 2002 a , b ); Sadler et al (2000); Sandodden et al (2001); Sharpe (2007); Sharpe et al (1998); Sink et al (2007); Skjervold et al (2001); Sloman et al (2001); Smith et al (2004); Stone et al (2008); Stratholt et al (1997); Sumpter et al (1985); Tanck et al (2000); Thomas et al (1999); Van Dijk et al (1993); Vianen et al (2001); Waring et al (1992); Weber et al (2002); Winberg & Lepage (1998); Yin et al (1995). (b) A box plot of the data presented in (a) where the boundary of the box closest to zero indicates the 25th percentile, the unbroken line within the box marks the median, the broken line denotes the mean and the...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… (a) Mean values for plasma cortisol levels in six cyprinid and eight salmonid species subjected to a range of stressors. The data plotted were obtained from: Aaltonen et al (2000); Barton (2000); Basu et al (2001); Bau et al (2001); Benfey & Biron (2000); Blahová et al (2007); Cairns et al (2008); Clements et al (2002); Congleton et al (2000); Dabrowska et al (1991); Davis & Schreck (1997); Dror et al (2006); Einarsdóttir & Nilssen (1996); Elofsson et al (2000); Fevolden et al (1999); Gagnona et al (2006); Høgåsen & Prunet (1997); Iversen et al (1998); Jeney et al (1996); Jhingan et al (2003); Jørgensen et al (2001, 2002); Kagawa & Mugiya (2000); Kakuta (1998); Kubokawa et al (1999); Lister et al (2008); McDonald & Robinson (1993); McDonald et al (1993); Mesa (1994); Mesa et al (2000); Momoda et al (2007); Øverli et al (1999); Pankhurst & Dedual (1994); Pankhurst et al (2008); Pickering et al (1982, 1986); Pottinger & Carrick (2000); Pottinger & Moran (1993); Pottinger (1998); Pottinger et al (1992, 1999, 2000); Quabius et al (2000); Quigley et al (2006); Reddy et al (1995); Ruane et al (1999, 2001, 2002 a , b ); Sadler et al (2000); Sandodden et al (2001); Sharpe (2007); Sharpe et al (1998); Sink et al (2007); Skjervold et al (2001); Sloman et al (2001); Smith et al (2004); Stone et al (2008); Stratholt et al (1997); Sumpter et al (1985); Tanck et al (2000); Thomas et al (1999); Van Dijk et al (1993); Vianen et al (2001); Waring et al (1992); Weber et al (2002); Winberg & Lepage (1998); Yin et al (1995). (b) A box plot of the data presented in (a) where the boundary of the box closest to zero indicates the 25th percentile, the unbroken line within the box marks the median, the broken line denotes the mean and the...…”
Section: Resultsmentioning
confidence: 99%
“…In O. mykiss trout, post‐stress cortisol levels (following a standardized 2 h confinement) ranged from c. 50 ng ml −1 at 10° C to 100 ng ml −1 at 16° C (Pottinger & Carrick, 2000). For R. rutilus post‐stress cortisol levels were c. 400 ng ml −1 when water temperature was 5° C and 600 ng ml −1 at a temperature of 15° C (Pottinger et al , 1999). While these data suggest that higher maximum cortisol values were obtained at similar time points at the higher temperature, it would be reasonable to assume on the basis of the earlier results that modulation of the stress response by the relatively small temperature difference (3° C) between the two sets of tests in the current study did not obscure underlying differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated glycemia in fish, as a response to stress, is due to the action of catecholamines which stimulate glycogenolysis, while increased levels of plasma glucose are maintained by cortisol, which acts after adrenalin (Wijayan et al 1994). Hyperglycemia is generally observed in animals exposed to some type of adverse stimulus (Pottinger et al 1999). However, in the same manner as with cortisol, it is not known with certainty at what time glucose levels peak after a stress stimulus, for the species in question.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, some inconsistencies have been reported in the results of several experimental studies, much of them associated with undefined and uncontrolled variables, which may alter the secretion of cortisol and glucose into the bloodstream. Most of these factors are not considered as direct stressors but have an effect on the intensity of the response which makes them a source of error (Kawauchi et al 1984;Davis and Parker 1990;Vijayan and Leatherland 1990;Lamers et al 1991;Sun et al 1992;Sun et al 1995;Reid et al 1998;Wilson et al 1998;Arends et al 1999;Fevolden et al 1999;Mommsen et al 1999;Pottinger et al 1999 Mass mortality of fish was observed following a sudden cold shock (15 °C decreases in water temperature from 27 °C to 12 °C over 24 h) in matrinxã (Brycon cephalus). In addition, a sudden 12 °C decrease in water temperature (from 27 °C to 15 °C over 24 h) caused 20% mortality in this fish species.…”
Section: Discussionmentioning
confidence: 99%